Klanceng Honey (Tetragonula laeviceps): Its effect on fasting blood glucose, lipid and hematological profiles, and pancreatic histopathology of diabetic rats - Agussalim; Umami, Nafiatul; Nurliyani; Wan Ismail, Wan Iryani; Masyithoh, Dewi; Ustadi; Agus, Ali (Communications in Science and Technology, 2024)
This study aims to assess the daily ingestion of Klanceng Honey (KH) on fasting blood glucose (FBG), high-density lipoprotein (HDL), total cholesterol (TC), triglyceride (TG), low-density lipoprotein (LDL), and pancreatic histopathology. Thirty rats were involved and divided into six groups: G1 = untreated normal rats, G2 = untreated diabetic rats (DR), G3 = DR treated with 0.9 mg/kg BW glibenclamide, G4, G5, and G6 = DR treated with 1, 2, and 3 g/kg BW KH, respectively for 28 days. The FBG level of G1 was found lower than that of diabetic rat groups (G2–G6) (p<0.01). The TC level of G1 group on 14th and 28th days was lower than that of G2–G6 groups (p<0.01). The TG levels in all rat groups showed no significant difference at 0–28 days. On 14th day, the LDL level of diabetic groups were higher than the one in G1 group (p<0.01). Meanwhile, on 14th and 28th, the HDL levels of G3–G6 groups, were higher than the one in G1 group (p<0.01). The pancreatic histopathology of all rat groups showed no abnormalities of the Langerhans islets. The daily ingestion of KH prevented FBG, TC, TG, and LDL levels from rising, increased the HDL levels, and protected the pancreatic glands against damage. T. laeviceps honey can potentially be used as a functional food for therapy of DM patients.